2013
DOI: 10.1099/jmm.0.047365-0
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis of Tritrichomonas foetus-infected bulls, an ultimate approach to eradicate bovine trichomoniasis in US cattle?

Abstract: Diagnosis ofBovine trichomoniasis is a sexually transmitted protozoan disease with a worldwide distribution. It has been endemic in the USA for more than 80 years. Mississippi and all the states west of the Mississippi River, except Iowa and Minnesota, have rules/regulations to reduce the spread of the disease. The core of these regulations consists of testing bulls and prohibiting importation of nonTritrichomonas foetus-free bulls. Factors such as sampling methods and intervals, shipping medium and temperatur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
65
0
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 58 publications
(69 citation statements)
references
References 47 publications
2
65
0
2
Order By: Relevance
“…Bovine trichomoniasis is distributed worldwide, with cases reported in America, Asia, Australia, Europe and South Africa where natural bull service is a means of cattle breeding (Yao, 2013). T. foetus undergoes only the trophozoite stage and is mainly transmitted between bulls and cows/heifers by coitus.…”
Section: Introductionmentioning
confidence: 99%
“…Bovine trichomoniasis is distributed worldwide, with cases reported in America, Asia, Australia, Europe and South Africa where natural bull service is a means of cattle breeding (Yao, 2013). T. foetus undergoes only the trophozoite stage and is mainly transmitted between bulls and cows/heifers by coitus.…”
Section: Introductionmentioning
confidence: 99%
“…12 Using the pooling methodology outlined in the present study, a slight difference in sensitivity was observed between the 1/5 and 1/3 sample pools when compared to testing the samples individually. Utilizing the study laboratory's protocol, pooling at a 1/5 dilution produced better sensitivity than the average reported sensitivity (approximately 90%) for a single cultured smegma sample tested by microscopy 5,8,15 and was equivalent to the stated sensitivity of 95% or higher, 21 obtained by collecting and culturing 3 separate smegma samples with 7 days of sexual rest between collections. Compared to nPCR and sequencing results, 1/5 pools had a kappa value of 91% that was equivalent to individual sample testing in 3 of the 5 feeder laboratories.…”
Section: Discussionmentioning
confidence: 99%
“…5,8,15 Specificity may also be compromised given the ability of other protozoa with morphology similar to T. foetus to be present in the bull's prepuce. 6,9 To increase the sensitivity of culture to 95% or more, it was calculated that 3 successive cultures, at least 7 days apart were necessary, 21 thus making this diagnostic process slow and expensive. Alternatively, many diagnostic laboratories and state regulatory agencies have modified and adopted a quantitative polymerase chain reaction (qPCR) 13 method that offers a rapid, quantitative, and more accurate detection system when compared to the classical microscopy method.…”
Section: Introductionmentioning
confidence: 99%
“…Tritrichomonas foetus TF) is a sexually transmitted protozoon that causes reproductive failure so disruptive among cattle that virtually all US states west of the Mississippi River have initiated control programs [1]. Each of these control programs is based on the testing and exclusion of individual bulls.…”
Section: Introductionmentioning
confidence: 99%